6–12 GHz double-balanced image-reject mixer MMIC in 0.25 µm AlGaN/GaN technology. Issue 3 (30th March 2015) - van Heijningen, Marc; Hoogland, Jeroen A.; de Hek, Peter; van Vliet, Frank E.
Abstract : The front-end circuitry of transceiver modules is slowly being updated from GaAs-based monolithic microwave integrated circuits (MMICs) to Gallium-Nitride (GaN). Especially GaN power amplifiers and T/R switches, but also low-noise amplifiers (LNAs), offer significant performance improvement over GaAs components. Therefore it is interesting to also explore the possible advantages of a GaN mixer to enable a fully GaN-based front-end. In this paper, the design-experiment and measurement results of a double-balanced image-reject mixer MMIC in 0.25 μm AlGaN/GaN technology are presented. First an introduction is given on the selection and dimensioning of the mixer core, in relation to the linearity and conversion loss. At the intermediate frequency (IF)-side of the mixer, an active balun has been used to compensate partly for the loss of the mixer. An on-chip local-oscillator (LO) signal amplifier has been incorporated so that the mixer can function with 0 dBm LO input power. After the discussion of the circuit design the measurement results are presented. The performance of the mixer core and passive elements has been demonstrated by measurements on a test-structure. The mixer MMIC measured conversion loss is <8 dB from 6 to 12 GHz, at 1 GHz IF and 0 dBm LO power. The measured image rejection is better than 30 dB.